ASPEK HUKUM PIDANA DALAM PERJUDIAN SECARA ONLINE - PURNAWINATA, DODY TRI (Faculty of Law, University of Palembang, 2021)
Advances in the world of information and technology provide a new way of online gambling. There are many difficulties in uncovering an online gambling case either to determine the perpetrators of online gambling as well as to determine the place and time of the occurrence of a criminal act of online gambling as well as legal liability for the offender. The materials used in this law research are primary legal materials, secondary, and tertiary. The collection of legal materials research done by identifying, inventorying legislation, researching material library, reading books and other resources related to the problem being studied. Legal materials that have been collected and processed with the interpretation of legal materials and then deduced to draw conclusions about determining the perpetrators, determining locus and tempus delicti and legal liability of online gambling as criminal act in normatif explanantion. The result of this study that in determining the perpetrators of online gambling should be filled ellement are attached to the subject of law (subjective) and attached to the deed (objective), in this case commonly used theories in Indonesia related to locus and tempus delicti can be used in determining locus and tempus delicti relating to the competence of the court,although with advances in technology make it possible for the perpetrator to decieve the real locus and tempus. Legal liability of the offender based on person’s condition to be liable for their actions regardless of their justification and excuse.